Macular corneal dystrophy with isolated peripheral Descemet membrane deposits - Zhang, Wenlin (Am J Ophthalmol Case Rep, 2019)
PURPOSE: Macular Corneal Dystrophy (MCD, MIM #217800) is a category 1 corneal stromal dystrophy as per the current IC3D classification. While characterized by macular stromal deposits, we report a case of MCD type II with isolated bilateral peripheral Decemet membrane opacities, describing the clinical features and results of screening the CHST6 gene and serum sulfated keratan sulfate levels. OBSERVATIONS: A 68-year-old man with an unremarkable past medical and family history presented with bilateral progressive decrease in vision. Ocular exam revealed bilateral clear corneas with the exception of peripheral, round, gray-white discrete deposits at the level of Descemet membrane and decreased central corneal thickness in both eyes. The morphology of the corneal deposits, decreased corneal thickness and the absence of a family history were consistent with MCD, prompting screening of the CHST6 gene. Sanger sequencing followed by allele specific cloning revealed compound heterozygous CHST6 mutations in trans configuration: c.-26C > A, which created a new upstream open reading frame (uORF’), predicted to attenuate translation efficiency of the downstream main ORF; and c.803A > G (p.(Tyr268Cys)), previously associated with MCD. Serum keratan sulfate was reduced but detectable, consistent with the diagnosis of macular corneal dystrophy type II. CONCLUSIONS: Although macular corneal dystrophy is classified as a corneal stromal dystrophy with endothelial involvement, we report a case of MCD with dystrophic deposits confined to the peripheral Descemet membrane, indicating that MCD may be associated with isolated endothelial involvement.